2017
DOI: 10.1111/jiec.12594
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy and Carbon Management in the Cradle‐to‐Cradle Certification: Limitations and Opportunities

Abstract: Summary 11As part of the Cradle to Cradle ® (C2C) certification program, the C2C certification criterion 12 "Renewable Energy and Carbon Management" (RE&CM) focuses on use of electricity from RE 13 and direct greenhouse gas offsets in the manufacturing stage and to a limited extent on the cradle to 14 gate only at the highest level of certification. The aim of this study is to provide decision-makers 15 with a quantified overview of possible limitations of that C2C certification requirement and 16 potential ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Cleaner production (Bhandari et al, 2019); (Jia et al, 2019); (Vimal et al, 2019); (Mendoza et al, 2019); (Kalmykova et al, 2018); (Niero et al, 2018); (Fisher et al, 2018); (Ridaura et al, 2018); (Zhong and Pearce, 2018a); (Minunno et al, 2018); (Franciosi et al, 2017); (Despeisse et al, 2017); (Ingarao, 2017); (Trentesaux and Giret, 2015); (Paredes-Sánchez et al, 2018).…”
Section: Decision Supportmentioning
confidence: 99%
“…Cleaner production (Bhandari et al, 2019); (Jia et al, 2019); (Vimal et al, 2019); (Mendoza et al, 2019); (Kalmykova et al, 2018); (Niero et al, 2018); (Fisher et al, 2018); (Ridaura et al, 2018); (Zhong and Pearce, 2018a); (Minunno et al, 2018); (Franciosi et al, 2017); (Despeisse et al, 2017); (Ingarao, 2017); (Trentesaux and Giret, 2015); (Paredes-Sánchez et al, 2018).…”
Section: Decision Supportmentioning
confidence: 99%
“…Bach, Minkov and Finkbeiner (2018) found that good environmental performance of CTC certified products is not assured due to the limited assessment scope, which does not take into account all product life-cycle phases and disregards some environmental impacts. Others have also argued that CTC design might shift the focus of design decisions from the entire life cycle of the product to the minimisation or eliminatation of toxic materials; therefore, it might result in the impacts of energy consumption being overlooked (Bakker et al, 2010;Llorach-Massana, Farreny, & Oliver-Solà, 2015;Niero et al, 2018). This is a particularly significant issue for products which consume energy during the use phase (Llorach-Massana et al, 2015).…”
Section: Compliance Requirementsmentioning
confidence: 99%
“…It is important to acknowledge the complementariness of eco-efficiency (measured by LCAs) and eco-effectiveness rather than treating them as mutually exclusive and contrasting. To address this, several studies have argued for the complementary use of CTC and LCA in design practice (see, e.g., Bjørn & Hauschild, 2013;Toxopeus, de Koeijer, & Meij, 2015;Niero et al, 2018). Nevertheless, there have so far been no significant contributions on this front.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…We considered the introduction of a broader RE perspective covering the life cycle, and our results showed that increasing the share of RE in the primary aluminum production from a full life cycle perspective can greatly increase the environmental benefits brought up by the C2C certification not only for climate change, but for the broader range of impact categories (Niero et al. ).…”
Section: Recommendations and Perspectivesmentioning
confidence: 99%